Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP Kelas VII Materi Segi Empat Berdasarkan Kecemasan Matematika - Lasdianto, Jasmine Ramadhani; Haerudin, Haerudin; Abadi, Agung Prasetyo (Program Studi Sarjana Pendidikan Matematika, Universitas Singaperbangsa Karawang, 2024)
The purpose of this study was to analyze the mathematical problem solving abilities of seventh grade junior high school students on rectangular material based on the level of mathematics anxiety. This type of research is descriptive qualitative research. The research subjects were 3 students of class VIII A of Cirebon State Junior High School. Taking the subject using purposive sampling technique. The data analysis technique consisted of a description of the results of the questionnaire, written tests and interviews, then the results of the written tests and interviews were analyzed, then conclusions were drawn. The results showed that students with low levels of mathematics anxiety were able to pass all indicators, namely being able to understand the existing problem, able to make a settlement plan according to what was known, and able to carry out the completion plan and re-examine the answers obtained so as to get the right results. Students with moderate levels of anxiety are able to pass two indicators, namely being able to understand the problem and make a settlement plan according to what is known and asked, but unable to carry out the completion plan and re-examine the answers so that they get incorrect results. Students with a high level of math anxiety are only able to pass one indicator, namely being able to understand the problem, but not being able to draw up a settlement plan according to what is known and asked, carry out the completion plan and re-examine the answers so that they get incorrect results. Keywords: Problem Solving Ability, Anxiety Level, Quadrangle.